PENGARUH STATUS SOSIAL EKONOMI ORANG TUA DAN LITERASI EKONOMI TERHADAP PERILAKU KONSUMSI MAHASISWA UNIVERSITAS HAMZANWADI - Baiq Yuliana Rizkiwati; Abdul Gunawan; Huzain Jailani; Muhammad Zainul Majdi (Lembaga Bale Literasi, 2023)
This study aims to: 1) To partially determine the Influence of Parents' Socioeconomic Status and Economic Literacy on The Consumption Behavior of Hamzanwadi University. 2) To find out whether simultaneously the Socioeconomic Status of Parents and Economic Litration have a significant effect on the Consumption Behavior of Hamzanwadi University. 3) To find out the most dominant factor affecting the Consumption Behavior of Hamzanwadi University. The method used is a quantitative method. The population used in this study are parents and students of Universias Hamzanwadi who have different Parental Economic Status to the Consumption Behavior of Hamzanwadi University and sampling techniquesuses purposive random sampling. Data collection is in the form of distributing questionnaires. The data analysis techniques in this study are classical assumption testing, multiple regressionlinary, and hypothesis testing. The results showed variables (1) Economic Status of Parents (X1) towards Student Consumption Behavior (Y) Economic of Hamzanwadi University. From the results of the study that it has no effect on the Consumption Behavior of Hamzanwadi university both pesially and simultaneously because the Socioeconomic Status of Parents has a sign value of 0.392 > 0.05 and a calculated t value of 0.898 0.05 and a calculated value of 1.089 < 4.044 so it can be concluded that there is no influence of Parents' Socioeconomic Status on Student Consumption. (3) From the two discussions above, the variables of Socioeconomic Status of Old Orag (X1) and Economic Literacy (X2) have no effect either initially and simultaneously on Student Consumption (Y) Study on Economic Education of Hamzanwadi University because in accordance with the results of the researchers above, it shows that the significance value of the Influence of Socioeconomic Status of Parents (X1) and Economic Literacy (X2) on Student Consumer Behavior (Y) is 0.360 > 0.05 and the value of F count 1.147 < 4.044, so it can be concluded that only HO is accepted while H1, H2 and H3 are rejected. This means that there is no significant, partial and simultaneous influence of Socioeconomic Status of Parents (X1) and Economic Literacy (X2) on Student Consumption Behavior (Y).